1999
DOI: 10.1073/pnas.96.16.9427
|View full text |Cite
|
Sign up to set email alerts
|

Chemoreceptor discharges and cytochrome redox changes of the rat carotid body: Role of heme ligands

Abstract: In superfused in vitro rat carotid body, we recorded chemoreceptor discharges and the redox state of cytochromes simultaneously to identify the primary oxygensensing protein controlling transmitter release and electrical activity of the carotid sinus nerve. These parameters were tested under the inf luence of heme ligands such as oxygen, cyanide, 4-(2-aminoethyl)-benzenesulfonyl f luoride, and CO. During stimulation, there was an initial increase in discharge frequency followed by a decline or suppression of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 37 publications
1
42
1
Order By: Relevance
“…In new experiments we have found that AEBSF enhances hypoxia-evoked CSN activity in the rat carotid body (Fig. 5), a result which conflicts with earlier studies (Lahiri et al, 1999). Collectively, these recent findings strongly suggest that ROS generated by Nox enhance maxiK-like currents, and promote cell repolarization.…”
Section: Chemoreceptor Function In Normal and Nox-gene-deleted Cellscontrasting
confidence: 56%
See 2 more Smart Citations
“…In new experiments we have found that AEBSF enhances hypoxia-evoked CSN activity in the rat carotid body (Fig. 5), a result which conflicts with earlier studies (Lahiri et al, 1999). Collectively, these recent findings strongly suggest that ROS generated by Nox enhance maxiK-like currents, and promote cell repolarization.…”
Section: Chemoreceptor Function In Normal and Nox-gene-deleted Cellscontrasting
confidence: 56%
“…Furthermore, certain subunits common to the phagocyte and non-phagocyte forms of the enzyme, including p22 phox , gp91 phox (or a closely related Nox isoform), p47 phox , and p67 phox , have been localized to type I cells by immunocytochemical staining (Kummer and Acker, 1995). The spectral absorption studies of Acker and his colleagues have enhanced the Nox hypothesis by showing that hypoxia reduces an isoform of cytochrome b558 (Lahiri et al, 1999). Also, a specific Nox inhibitor, 4-(2-aminoethyl)-benzenesulfonyl fluoride (AEBSF), was shown to first excite carotid sinus nerve activity, and then block the chemorecptor response to hypoxia (Lahiri et al, 1999).…”
Section: Diverse Views Of Nox Function In Carotid Bodymentioning
confidence: 92%
See 1 more Smart Citation
“…1,2,[9][10][11][12] The 2 types of O 2 sensors that regulate ventilation and EPO production in response to changes in arterial oxygen concentration are not completely understood and, to some extent, are still the subject of controversy. 1 Although the oxygen sensors for the HVR in the carotid body and in certain other chemoreceptors have been identified as NADPH oxidase isoforms [13][14][15][16][17] (reviewed in Dröge 18 ), the regulation of EPO production was shown to involve activation of the hypoxia-inducible transcription factor (HIF), which depends on redox-sensitive stabilization of its ␣ subunit. 19,20 Oxygensensing involves in this case the oxygen-dependent hydroxylation of a proline residue (HIF-1␣ P564) and the subsequent ubiquitination and degradation of HIF-1␣.…”
Section: Introductionmentioning
confidence: 99%
“…Candidates for oxygen-sensor molecules in glomus cells include cytochrome aa 3 Mills and Jobsis 1972;Wilson et al 1994), K + -channels (Buckler 1997;Lopez-Barneo 1996;Wyatt et al 1995), and NADPH oxidases generating reactive oxygen species (ROS; Acker et al 1989;Cross et al 1990). These NADPH oxidases and the mitochondrial respiratory chain are sources of ROS, and altered ROS production during hypoxia has been suggested to be part of the intracellular signaling cascade in response to hypoxia (Acker et al 1989(Acker et al , 1992Cross et al 1990;Lahiri et al 1999). Another free radical, nitric oxide (NO), modulates the response of the carotid body to hypoxia, either directly by inhibition of chemoreceptor activity (Iturriaga et al 2000a,b;Prabhakar et al 1993;Prabhakar 1999;Wang et al 1994Wang et al , 1995 or indirectly by affecting vascular tone and, thereby, O 2 delivery (Lahiri et al 2001).…”
Section: Introductionmentioning
confidence: 97%